87.0k views
3 votes
-2(1-3x)=22-3(x-13) please help

1 Answer

5 votes

Let's solve this problem step by step.

−2(1−3x)=22−3(x−13)

Step 1: Simplify both sides of the equation.

(−2)(1)+(−2)(−3x)=22+(−3)(x)+(−3)(−13)(Distribute)

−2+6x=22+−3x+39

6x−2=(−3x)+(22+39)(Combine Like Terms)

6x−2=−3x+61

Step 2: Add 3x to both sides.

6x−2+3x=−3x+61+3x

9x−2=61

Step 3: Add 2 to both sides.

9x−2+2=61+2

9x=63

Step 4: Divide both sides by 9.

9x/9=63/9

So, the answer to this problem is x=7.

User Mario Lamacchia
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.